2018
DOI: 10.3390/ijms19051361
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Activity of Orally Administered Curcumin Incorporated in Eudragit®-Containing Liposomes

Abstract: Curcumin is an antimalarial compound easy to obtain and inexpensive, having shown little toxicity across a diverse population. However, the clinical use of this interesting polyphenol has been hampered by its poor oral absorption, extremely low aqueous solubility and rapid metabolism. In this study, we have used the anionic copolymer Eudragit® S100 to assemble liposomes incorporating curcumin and containing either hyaluronan (Eudragit-hyaluronan liposomes) or the water-soluble dextrin Nutriose® FM06 (Eudragit-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…The positive control used in the test was 0.1% Triton X-100, which caused extensive erythrocyte lysis. The results are in agreement with previous studies that indicate low hemolysis by Eudragit nanoparticles (Coma-Cros et al, 2018) and some essential oils at concentrations above 1 mg/ml (Fabri et al, 2019;Sobrinho et al, 2016).…”
Section: Hemolytic Activitysupporting
confidence: 93%
“…The positive control used in the test was 0.1% Triton X-100, which caused extensive erythrocyte lysis. The results are in agreement with previous studies that indicate low hemolysis by Eudragit nanoparticles (Coma-Cros et al, 2018) and some essential oils at concentrations above 1 mg/ml (Fabri et al, 2019;Sobrinho et al, 2016).…”
Section: Hemolytic Activitysupporting
confidence: 93%
“…Eudragitnutriosomes presented better performance than Eudragithyaluronan liposomes due to the greater stability of the former, as shown by the vesicle behavior in gastrointestinal fluids. 64 Several studies have tried to target liposomes encapsulating PQ to the liver stage of malaria. 65 In P. berghei infections in mice, liposomes could decrease the toxicity of parenteral PQ delivery, which allowed for the administration of higher doses and resulted in the cure of the animals following a single intravenous injection.…”
Section: Liposomesmentioning
confidence: 99%
“…Curcumin (1,7-bis (4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3, 5-dione; also called diferuloylmethane, Figure 1) is a polyphenolic phytochemical extracted from the root of Curcuma longa, commonly called turmeric. Numerous studies have shown the antioxidant [1,2], anti-inflammatory [3,4], antimalarial [5,6] and neuroprotective properties [7,8] of curcumin. Moreover, cell culture experiments have shown the antitumor activity of curcumin in various human cancer cell lines, such as leukemia [9], esophageal cancer [10], gastric cancer [11], liver cancer [12], lung cancer [13] and cervical cancer [14].…”
Section: Introductionmentioning
confidence: 99%